A Critical Review of Smart Residential Environments for Older Adults With a Focus on Pleasurable Experience - Lee, Li Na; Kim, Mi Jeong (Frontiers in Psychology, 2020)
Various smart services and technologies have been developed to support older adults’ wellness, make their daily tasks easier and enhance their overall quality of life. Typically, older adults desire to continue staying in their own residences but are unwilling to make significant home modifications. However, when people grow older, they inevitably experience a significant decrease in their physical, cognitive, and sensory capabilities, which makes them develop negative attitudes towards technology. Older adults eventually need some form of help from caregivers or community resources to live independently and accomplish daily tasks. In this regard, this study highlights that older adults require not only usable and practical spaces but also smart environments that can fulfill them emotionally. Research on smart environments for this population should consider the hedonic and experiential factors of interacting with technology, such as fun, fulfilment, play, and user engagement. This study aims to provide a comprehensive review of smart environments to support positive aging and pleasurable user experience in the architecture domain. For this critical review emphasizing the pleasurable smart environment, an evaluation framework was developed, consisting of four categories: wellness, independence, acceptance, and design. Through an extensive analysis of selected papers in the architecture domain, it was found that studies on the smart home tend to focus on utilitarian factors, such as usability, monitoring physical experiences, and simulating energy efficiency, and rarely mention psychological wellness. Smart environments should be designed to not only emphasize efficiency, effectiveness, and satisfaction but also to engage older adults and provide them positive experiences. As various smart technologies continue to evolve and integrate into smart living spaces, it is important to understand older adults’ cognitive and emotional aspects and make the smart environment a more comfortable place for them.